2013
DOI: 10.1016/j.ejso.2013.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of radical cystectomy and urinary diversion complications with the Clavien classification system in an Italian real life cohort

Abstract: Introduction: Standardized methods of reporting complications after radical cystectomy (RC) and urinary diversions (UD) are necessary to evaluate the morbidity associated with this operation to evaluate the modified Clavien classification system (CCS) in grading perioperative complications of RC and UD in a real life cohort of patients with bladder cancer. Materials and methods: A consecutive series of patients treated with RC and UD from April 2011 to March 2012 at 19 centers in Italy was evaluated. Complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 23 publications
5
36
1
5
Order By: Relevance
“…However, previous studies failed to show higher complication rates for advanced diseases compared to localized tumours. 2,3,5,7 Nonetheless, further investigations are needed to comprehensively address this issue. Additionally, the NSQIP database lacked information regarding gastrointestinal complications, which has been shown to occur in a substantial proportion of patients after RC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous studies failed to show higher complication rates for advanced diseases compared to localized tumours. 2,3,5,7 Nonetheless, further investigations are needed to comprehensively address this issue. Additionally, the NSQIP database lacked information regarding gastrointestinal complications, which has been shown to occur in a substantial proportion of patients after RC.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported predictors of complications, perioperative mortality, and readmission. However, these data are usually obtained from tertiary referral centres, 2,[5][6][7] and therefore may not be generalizable to the American population. Recent population-based studies have reported nationwide outcomes for patients treated with RC for bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary infections represent one of the major complications in patients affected by UCS, crucially determining a decreasing of renal functionality over time [2]. An early diagnosis is fundamental to improve the prognosis and block the progression, hence, allowing for therapy [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, open radical cystectomy (ORC) is still the gold standard approach, but a significant morbidity, high complication rate and mortality is still related to this technique [2,3,4]. More recently, robot-assisted radical cystectomy (RARC) has emerged as an attractive alternative to ORC, aiming to reduce morbidity and complications, and to potentially improve peri-operative and functional outcomes [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%